In vitro stimulation of lymphocytes by mycoplasma synoviae derived mitogen - Mojca NARAT (Acta Agriculturae Slovenica)
Mycoplasma synoviae causes infections of the upper respiratory tract of chickens and turkeys. In poorly defined conditions infection results in an arthritic disease, infectious synovitis . Studying this synovitis as an animal model of an autoimmune arthritis we have examined the presence, location and potential of Mycoplasma synoviae mitogenic factor, which could trigger the induction of infectious synovitis. In the study described herein in vitro mitogenic activity of membrane fraction and culture supernatant preparations of four Mycoplasma synoviae strains was demonstrated. Active fraction from culture supernatant of Mycoplasma synoviae AAY-30 strain was more than twice as active as its membrane preparation. This activity resides to the soluble protein, which is active for chicken and mouse thymic cells and for human peripheral lymphoctyes. The culture supernatant mitogenic factor is a protein with molecular weight of about 60 kD and pI of about 4.0.